2018
DOI: 10.1016/j.jmii.2016.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with outer membrane proteins (OprF and OprI) and flagellin B protects mice from pulmonary infection with mucoid and nonmucoid Pseudomonas aeruginosa

Abstract: Our data showed that mice immunized with OprF/OprI or OprF/OprI and flagellin B are significantly protected from infection caused by mucoid and nonmucoid strains of P. aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 34 publications
0
21
1
Order By: Relevance
“…In addition, these proteins are important for maintaining the integrity of the outer membrane and can stimulate strong antibody responses, with anti-OmpA family proteins antibodies reported to be bactericidal, opsonic, and protective ( Zhang et al, 2016 ; Kazemi Moghaddam et al, 2017 ; Maccarini et al, 2017 ; Tang et al, 2017 ). As a result, OmpA family proteins are promising candidates for vaccine development, and these proteins from a number of bacteria have been reported to be able to induce protective immunity against bacterial infection, some vaccines contain OmpA family proteins even entered phase III clinical trials, such as OprF from P. aeruginosa ( Price et al, 2001 ; Oldfield et al, 2008 ; Peluso et al, 2010 ; Ayalew et al, 2011 ; Hounsome et al, 2011 ; Westritschnig et al, 2014 ; Zhang et al, 2016 ; Hassan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these proteins are important for maintaining the integrity of the outer membrane and can stimulate strong antibody responses, with anti-OmpA family proteins antibodies reported to be bactericidal, opsonic, and protective ( Zhang et al, 2016 ; Kazemi Moghaddam et al, 2017 ; Maccarini et al, 2017 ; Tang et al, 2017 ). As a result, OmpA family proteins are promising candidates for vaccine development, and these proteins from a number of bacteria have been reported to be able to induce protective immunity against bacterial infection, some vaccines contain OmpA family proteins even entered phase III clinical trials, such as OprF from P. aeruginosa ( Price et al, 2001 ; Oldfield et al, 2008 ; Peluso et al, 2010 ; Ayalew et al, 2011 ; Hounsome et al, 2011 ; Westritschnig et al, 2014 ; Zhang et al, 2016 ; Hassan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the past two decades, a number of different vaccines and several monoclonal antibodies have been developed for active and passive vaccination against P. aeruginosa infection ( Pier, 2005 ; Priebe and Goldberg, 2014 ; Vincent, 2014 ; Grimwood et al, 2015 ; Le Moigne et al, 2016 ). The antigens used in these studies include lipopolysaccharides ( Pier, 2007 ), surface polysaccharides ( Pier, 2000 ), outer membrane proteins ( Gao et al, 2017 ; Rello et al, 2017 ), secreted proteins ( Hamaoka et al, 2017 ; Yang et al, 2017 ), flagella ( Hassan et al, 2017 ), and pili ( Ohama et al, 2006 ; Banadkoki et al, 2016 ). Several vaccine candidates even entered phase II/III clinical trials ( Baumann et al, 2004 ; Pier, 2005 ; Sharma et al, 2011 ; Le Moigne et al, 2016 ; Rello et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ceftolozane/tazobactam and ceftazidime/avibactam are new combinations of b-lactam/b-lactamase inhibitors that have been approved for use against certain infections caused by multidrug-resistant strains of P. aeruginosa (179). Vaccines using live-attenuated or irradiated P. aeruginosa (180)(181)(182), the LPS O-antigen (52), a 3-oxo-C12-HSL-carrier protein conjugate (183), and various recombinant proteins (PcrV [184,185], flagellin B [186], OprL [187], OprF [186], OprI [184,186], OprF/I fusion [188], pili [189,190], T6SS hemolysin coregulated protein 1 [184]) are being investigated to prevent P. aeruginosa infections. Because P. aeruginosa is a World Health Organization "Priority 1: Critical" pathogen in need of new approaches to treatment (19), preclinical models of biologics are being assessed (Table 1).…”
Section: Novel Therapeutic Interventionsmentioning
confidence: 99%
“…Due to the highly immunogenic nature of OprF, numerous studies have utilized the porin in pursuit of a P. aeruginosa vaccine (85,86). Many recent publications involving the administration of chimeric OprF fusion proteins have demonstrated acquired immunity to P. aeruginosa can be achieved in mammals (87)(88)(89)(90)(91). Hassan et al demonstrated that a recombinant trivalent OprF-OprI-flagellin vaccine significantly reduced mortality resulting from acute pneumonia in mice infected with mucoid and nonmucoid strains of P. aeruginosa (89).…”
Section: Intruder Alert: Oprf In Virulence and Immune Responsementioning
confidence: 99%
“…Many recent publications involving the administration of chimeric OprF fusion proteins have demonstrated acquired immunity to P. aeruginosa can be achieved in mammals (87)(88)(89)(90)(91). Hassan et al demonstrated that a recombinant trivalent OprF-OprI-flagellin vaccine significantly reduced mortality resulting from acute pneumonia in mice infected with mucoid and nonmucoid strains of P. aeruginosa (89). In addition, Gomi et al showed that in a cystic fibrosis mouse model, mice with preexisting P. aeruginosa lung infections that were immunized with an OprF-adenoviral vector exhibited increased bacterial clearance relative to those that were not immunized (90).…”
Section: Intruder Alert: Oprf In Virulence and Immune Responsementioning
confidence: 99%